Harmonization Of Islamic Religious Education Curriculum In Private Schools Of Thai And Indonesia: Harmonisasi Kurikulum Pendidikan Agama Islam di Sekolah Swasta Thailand dan Indonesia - Naily Syarafi; Sauqi Futaqi; Lailatul Maghfiroh (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Islamic Religious Education (PAI) plays a crucial role in shaping moral character and religious identity within diverse sociocultural contexts. Specific background: In Southeast Asia, countries like Indonesia and Thailand have distinct educational and religious frameworks, posing unique challenges in aligning national curriculum policies with local needs. Knowledge gap: Limited comparative research exists on how private Islamic schools implement PAI curricula under differing national systems. Aims: This study investigates how PAI curriculum policies are harmonized across national and local levels in MA Tanwirul Qulub, Indonesia, and Tarbiyatul Wathan, Thailand. Results: Findings reveal that Indonesia applies a top-down model emphasizing curriculum flexibility under the Independent Curriculum, allowing local adaptations. Conversely, Thailand uses a bottom-up approach where private schools independently develop PAI content within a secular national framework, balancing state requirements with local religious needs. Novelty: This study offers a rare cross-national qualitative comparison of curriculum harmonization in Islamic private schools, capturing both central policy dynamics and grassroots practices. Implications: The research suggests the need for adaptive curriculum policies that uphold Islamic values while accommodating sociopolitical contexts, promoting inclusive and locally relevant religious education in multicultural societies.Highlight : The study compares PAI curriculum policies in private schools in Indonesia and Thailand. Indonesia implements a top-down approach, while Thailand uses a bottom-up model based on local needs. Harmonization aims to balance national policies with local religious identities and needs. Keywords : Harmonization, PAI Curriculum, Private Schools, Indonesia, Thailand